2006
DOI: 10.2214/ajr.05.1697
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 64-MDCT in the Diagnosis of Ischemic Heart Disease

Abstract: In clinical routine, coronary CTA will primarily be used for risk stratification on a per patient basis. In the present study, coronary 64-MDCT showed a high diagnostic accuracy on both per patient and per segment analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
125
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(144 citation statements)
references
References 22 publications
11
125
0
8
Order By: Relevance
“…The diagnostic performance of CTCA known from previous single-source and dual-source 64-slice CT studies conducted in the retrospective ECG-gating mode [3,4] could be maintained using the low-dose technique. The comparable diagnostic accuracy of CTCA as compared to CA has been shown in previous studies and could again be confirmed by our results [3,6,18,19].…”
Section: Low-dose Ctcamentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnostic performance of CTCA known from previous single-source and dual-source 64-slice CT studies conducted in the retrospective ECG-gating mode [3,4] could be maintained using the low-dose technique. The comparable diagnostic accuracy of CTCA as compared to CA has been shown in previous studies and could again be confirmed by our results [3,6,18,19].…”
Section: Low-dose Ctcamentioning
confidence: 99%
“…A total of two patients were overestimated with low-dose CTCA when taking >70% as the cutoff value for significant stenosis. Overestimation of stenosis grading must not be considered a specific drawback of prospective ECG-gating itself [20], but similarly occurs with retrospective ECG-gating in the helical mode [3,4].…”
Section: Low-dose Ctcamentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, 15 studies have examined 64-slice technology for the evaluation of suspected CAD (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) (Figure 2). In these studies, 64-slice MDCT was able to assess 97% of all coronary artery segments visualized by both CCA and MDCT (Table 1), which is approximately 5% more than previous 16-slice technology.…”
Section: Assessment Of Significant Cad Using Mdctmentioning
confidence: 99%
“…Furthermore, when using patient-based analysis, defined as the presence of one or more significant coronary artery lesions in a study subject, sensitivity for 64-slice MDCT ranged between 88% to 100% in the 15 studies reviewed (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Additionally, in study populations with a low prevalence of CAD (32%), per-patient sensitivity remained very high (96%) (9).…”
Section: Assessment Of Significant Cad Using Mdctmentioning
confidence: 99%